Teaching with Styles: A Predictive Factor for Improved Students’ Learning Outcomes in Classrooms - Folasade Esther Jimola (Journal of Elementary and Secondary School, 2024)
The manner in which a teacher teaches and relates with students is influenced and controlled by some teacher-related factors such as the style of teaching. This study examines (i) the teaching styles adopted by Literature-in-English teachers, (ii) Literature-in-English students’ perception of and preference for teachers’ teaching styles, and (iii) whether teachers’ teaching styles predict students’ achievement and attitude toward Literature-in-English. The study was a descriptive research of the survey type that employed four research instruments. The study consisted of 759 respondents (127 Literature-in-English teachers and 632 public senior secondary school II Literature-in-English students) in Ekiti State, Nigeria. The data collected for this study were analyzed using descriptive and inferential statistics. It was evident in the research that Literature-in-English teachers employed delegator, facilitator, and role model teaching styles while expert and formal authority styles were the least. The findings revealed that teacher teaching style is a good a predictor of students’ achievement and attitude toward Literature-in-English. Based on these findings, profound pedagogical implications and relevant recommendations were made for concerned education stakeholders.